2015
DOI: 10.1155/2015/971628
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Stress and Strain around the Bayan Har Block in the Tibetan Plateau

Abstract: With the constraint of GPS observation, the tectonic deformation of the Bayan Har block and its periphery faults is investigated based on an elastoplastic plane-stress finite element model. The results show that the elastic model cannot explain the current GPS observation in the Bayan Har block. When East Kunlun fault and Yushu-Xianshuihe fault are under plastic yield state or high strain localization, the calculated velocities fit well with the observation values. It indicates that most of the current shear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…These block boundaries attract broad attention from Earth scientists because more than a dozen strong earthquakes occurred in the last half century. However, the Heishibeihu Fault (one of four subsidiary faults) determined to be the northwest margin of the Bayan Har block [43][44][45], has been neglected as an interblock subsidiary fault. The strain distributed between the ATF and the four subsidiary faults in our result confirmed that the subsidiary faults accommodate oblique convergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These block boundaries attract broad attention from Earth scientists because more than a dozen strong earthquakes occurred in the last half century. However, the Heishibeihu Fault (one of four subsidiary faults) determined to be the northwest margin of the Bayan Har block [43][44][45], has been neglected as an interblock subsidiary fault. The strain distributed between the ATF and the four subsidiary faults in our result confirmed that the subsidiary faults accommodate oblique convergence.…”
Section: Discussionmentioning
confidence: 99%
“…The geometric traces of subsidiary faults converge at the western end of the EKLF in this region. In previous studies, the Heishibeihu Fault (one of four subsidiary faults) was determined to be the northwestern margin of the Bayan Har block [43][44][45], which is considered to be the block with the most active boundaries in China. Compared with other broadly studied faults (ie., EKLF, Ganzi-yushu-Xianshuihe fault and Longmenshan fault) around the Bayan Har block [18,46,47], its northwestern margin faults have not been given the same attention and the relevant references can almost not be retrieved.…”
Section: Introductionmentioning
confidence: 99%